Targeted Systems in Cancer Treatment - Yuliya Tikhonova (Journal of Global Pharma Technology, 2019)
The World Health Organization (WHO) estimates that in 2015 cancer was the first or second leading death cause before the age of 70 in 91 out of 172 countries, and ranked third or fourth in the other 22. This study analyzes three main types of targeted cancer therapies: low molecular weight inhibitors; monoclonal antibodies; and immunotoxins. The low molecular weight inhibitors analyzed in the paper are Gleevec, Sprycel, VEGF targeting, Nexavar, Tykerb, Iressa, EGFR and HER2 Targeting, Torisel. The monoclonal antibodies include VEGF, EGFR and HER2, Herceptin, Avastin, CD20, Rituxan, Zevalin, Campath. The DAB389IL-2 (or Ontak - FDA Approved Medication for the Treatment of Acute T Cell Lymphoma) represents immunotoxins. It proves that depending on the location of the unregulated protein, different approaches are implemented. Monoclonal antibodies can block interactions and functions of unregulated proteins within the extracellular compartment, while low molecular weight inhibitors can reach proteins that are within the cell compartment. Currently, many of these drugs are used in combination with traditional cancer treatments to increase patient survival. As it was found, VEGF inhibitors, for example, Avastin, increased in low concentrations the survival time of patients with metastatic colorectal cancer from 13.8 to 21.5 months.Keywords: Low molecular weight inhibitors, Gleevec, Pro-angiogenic molecules, Monoclonal antibodies.